Bank Health Analysis Based on the RGEC Method and Its Effect on Profitability (Case Study at PT Bank Sulteng, Palu City) - Saputra, Egi; Zainuddin, Fatlina; Kasim, Yunus; Anisah, Anisah (Universitas Muhammadiyah Pontianak, 2026)
This study aims to analyze the financial health of PT Bank Sulteng using the RGEC method, consisting of Risk Profile (NPL), Good Corporate Governance (GCG), Earnings (BOPO), and Capital (CAR), and their influence on profitability measured by Return on Assets (ROA). The data were obtained from quarterly financial reports covering the 2017–2024 period and analyzed using multiple linear regression with SPSS version 30. The findings indicate that only BOPO significantly affects profitability, while NPL, GCG, and CAR do not. The study highlights the importance of operational efficiency as a key factor in improving profitability and sustaining financial performance at Bank Sulteng